EFFECTS OF WATER MANAGEMENT AND COMPOSTED SEWAGE SLUDGE SUBSTRATES ON THE GROWTH AND QUALITY OF CLONAL EUCALYPTUS SEEDLINGS - Gabira, Mônica Moreno; da Silva, Richardson Barbosa Gomes; Mateus, Caroline de Moura D’Andréa; Villas Boas, Roberto Lyra; da Silva, Magali Ribeiro (Floresta, 2020)
This study aimed to evaluate the effect of substrates made of composted sewage sludge and irrigation depths on the growth and quality of E. grandis x E. urophylla cuttings to optimize water management for each substrate. The substrates were obtained from sewage sludge composted with sugarcane bagasse or Eucalyptus bark, namely: composted sewage sludge with sugarcane bagasse (1:3 v:v); sewage sludge composted with Eucalyptus bark (1:3 v:v) and a mixture of both substrates in a volumetric proportion 2:1 (v:v). Commercial substrate composed of Sphagnum peat, vermiculite and rice husk (3:1:1 v:v: v) was used as a control. The irrigation depths tested were 11, 14 and 17 mm, applied in two daily applications. The substrates were physically and chemically characterized and height, stem diameter, shoot, root and total dry mass, Dickson quality index and root system conformation were measured to determine the growth and quality of seedlings. The substrates obtained through the composting of sewage sludge with sugarcane bagasse or Eucalyptus bark are fit for producing Eucalyptus cuttings, however, the water specificity of each substrate must be considered. Although an 11mm irrigation depth is indicted for the mixture of both substrates (2:1 v:v), a 17mm irrigation depth is needed for the sewage sludge composted with sugarcane bagasse (1:3 v:v) substrate.